Two new species of Telipogon (Orchidaceae: Oncidiinae) from Costa Rica - Bogarín, Diego; Pupulin, Franco; Pérez-Escobar, Oscar A. (Lankesteriana, 2024)
The Neotropical genus Telipogon (Orchidaceae: Oncidiinae), comprising approximately 250 species, exhibits remarkable species diversity in the humid, montane forests of southern Central America and the Tropical Andes. Telipogon, when broadly defined, encompasses both the large-flowered species that mimic tachinid flies and the small-flowered species formerly classified under Stellilabium. In Costa Rica, this genus includes 55 species, with 16 classified as small-flowered species. While the large-flowered species of Telipogon (in the strict sense) have been taxonomically revised, the small-flowered species have yet to be the subject of a thorough taxonomic revision. Our research aims to partially fill this gap by focusing on a comparative morphological analysis of two novel small-flowered Telipogon species. We describe and illustrate Telipogon lateritius and T. muntzii, both discovered in the humid mid-elevation forest of the Caribbean watershed in Cordillera de Talamanca, Costa Rica. Telipogon lateritius is notable for its distinctive brick-colored flowers, featuring sepals, petals, and lips striped in chestnut brown; the lateral sepals connate into a triangular-ovate synsepal, complemented by sparse, stiff pubescence at the base of the lip. Telipogon muntzii, although closely resembling T. anacristinae, differs in its unique olive-green flowers, sparse trichomes on the lip, narrowly oblong lateral lobes of the column, and a helmet-shaped median lobe of the column exclusively covered by simple trichomes. This study provides new additions for a future taxonomic revision of Telipogon in Costa Rica.